2023
DOI: 10.1039/d2ta08606a
|View full text |Cite
|
Sign up to set email alerts
|

Structured aqueous processed lignin-based NMC cathodes for energy-dense LIBs with improved rate capability

Abstract: The cost and environmental impact of Li-ion batteries can be reduced through aqueous processing of cathode materials. Here, we used aqueous processing to prepare lignin-based NMC111 cathodes for Li-ion batteries with enhanced rate capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The development of bio-based binders for the positive electrode, i.e., the cathode, in LIBs is more scarcely reported than for graphite- and Si-based anodes. The binder requirements and performance are more complex due to various applied cathode chemistries, such as LiFePO 4 (LFP), LiMnO 2 (LMO), and Li(Ni x Mn y Co z )O 2 for (x + y + z = 1) (NMC) [ 2 , 87 ]. Moreover, certain cathode materials, especially NMC and LMO, are highly sensitive to humid air and water, and their exposure can result in the formation of lithium carbonates and lithium hydroxide, which can affect the cyclic performance [ 91 ].…”
Section: Bio-based Binder Development For Cathodesmentioning
confidence: 99%
See 3 more Smart Citations
“…The development of bio-based binders for the positive electrode, i.e., the cathode, in LIBs is more scarcely reported than for graphite- and Si-based anodes. The binder requirements and performance are more complex due to various applied cathode chemistries, such as LiFePO 4 (LFP), LiMnO 2 (LMO), and Li(Ni x Mn y Co z )O 2 for (x + y + z = 1) (NMC) [ 2 , 87 ]. Moreover, certain cathode materials, especially NMC and LMO, are highly sensitive to humid air and water, and their exposure can result in the formation of lithium carbonates and lithium hydroxide, which can affect the cyclic performance [ 91 ].…”
Section: Bio-based Binder Development For Cathodesmentioning
confidence: 99%
“…Moreover, certain cathode materials, especially NMC and LMO, are highly sensitive to humid air and water, and their exposure can result in the formation of lithium carbonates and lithium hydroxide, which can affect the cyclic performance [ 91 ]. Several bio-based binder systems have been identified and investigated, such as lignin [ 47 , 87 , 88 ], sodium alginate [ 48 , 86 ], cellulose-based [ 89 , 90 , 92 , 93 ], tragacanth gum [ 43 ], and others [ 94 ]. It was shown that the modification of the pH in an LFP–CMC-based aqueous slurry can significantly reduce the oxidation of Fe(II) and the formation of Li 3 PO 4 on the electrode’s surface [ 95 , 96 ].…”
Section: Bio-based Binder Development For Cathodesmentioning
confidence: 99%
See 2 more Smart Citations
“…A binder is a significant contributor to the evolution of the electrode structure. The development of new binders with different functions has gradually become a key to solve the low ion transport performance. Building the efficient ion transport channels inside the electrodes and realizing the high-speed transport is one of the key research directions for future battery technologies. More specifically, the binder determines the microscopic and interfacial evolution during electrode fabrication through its own physical and chemical properties. Poly­(vinylidene fluoride) (PVDF) is a commonly used binder in LIBs owing to its electrochemical stability. However, the low ionic conductivity of PVDF results in a slow Li + diffusion rate, which, in turn, affects the reaction kinetics and further restricts the application of high-rate LIBs. Therefore, new binders with good adhesion properties and high-rate properties are significant for the manufacture of high-power LIBs.…”
Section: Introductionmentioning
confidence: 99%